EFFECT OF IMPELLER BLADE THICKNESS ON CRITICAL IMPELLER SPEED IN AN AGITATED VESSEL - LOGANATHAN MURUGANANDAM; DEVARAJULU CHITRA * (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The successful design and operation of solid-liquid agitators require proper prediction of critical impeller speed (Njs) needed to suspend solids. It depends on system and impeller geometry as well as the properties of both solid and liquid. In this research, the effect of impeller blade thickness on Njs required for complete suspension of solid particles was discussed. Experiments were performed in an agitated vessel of 0.29 m diameter with three impellers namely Rushton turbine (RT), Pitched blade turbine (PBT) and A320 impeller. The impeller thickness was varied as 1, 2, 3 and 4 mm. The results showed that with the increase in impeller blade thickness, the critical impeller speed decreased significantly and the power required for complete suspension increased. Modifications are made in the Zwietering correlation by considering the effect of the impeller blade thickness to improve the prediction of critical impeller speed.